MoU inked between UMP & Kakatiya University - Laili, Zulkepeli (Penerbit UMP, 2014)
Kuantan, May 15 - Universiti Malaysia Pahang (UMP) signed a memorandum of understanding with Kakatiya University that would pave the way for a better strategic partnership for both parties.